Diagnóstico de nematódios gastrintestinais e pulmonares em raça nativa bovinos curraleiro Pé-Duro e raça melhorada Nelore e Guzerá e bromatologia da pastagem em município do oeste maranhense - Gonzaga, Ludmila Nayara Ribeiro (2017)
The objective of this study was to diagnose the presence of gastrointestinal and pulmonary nematodes found in native cattle of Curraleiro “Pé-Duro” cattle race compared to improved breeds Nelore and Guzerá of mesoregionMaranhense West, considering the dry season (PS) and rainy (PC) and bromatologia of forage species in the years 2015-2016, parasitological and bromatológicos tests were performed on two properties (a and B), in extensive and semiextensivo creation system. The parasite often separated by race was in Nelore cattle (P.S = 60%, 47.61%, 33.33%) (P.C. = 9.52%); the Curraleiro race Foot-Hard (PC = 7.22%, 1.88%) (PS = 6.89%; 7.5%; 11.53%) and Guzerá (PC = 12.5%; 6, 06%). In the period in which only the Curraleiro race was examined (Apr / 2015) without cohabitation with other improved breeds the OPG was zero. In July / 2015, Curraleiro had 400 OPG, PC in Nov / 2015 and Apr / 2016 show 1,500 OPG. In PS in Aug / 2016, the Nelore cattle have high parasite load - 5,200 OPG two infective larvae (L3) and a larva of Dictyocaulus viviparus, followed by Curraleiro 1,300 OPG for superfamily Strongyloidea. In bromatologia we got to massaigrass (1 collected PB = 7.1%; NDF = 77%; FDA = 43.33% - Rainy Season) and Mombasa grass (2nd collection - PB = 7.31%; FDN = 66.53%, 36.60% 3 = FDA collected PB = 1.9%; FDN = 96.33; FDA = 60.33% - Dry Period). The Nelore are more sensitive and provide maintenance of parasitism on the environment. The Guzerá cattle were more resistant to infection by nematodes. The Curraleiro showed parasitic resistance when raised in isolation, but in cohabitation with other improved breeds have moderate infection of parasitism. The “Pé-Duro cattle showed resilience to parasitic infections and may present an alternative to genetic programs as parasitism control due to its hardiness and adaptation to the environment with well-defined dry periods. The PB, FDN and FDA are outside the standard set for the dry matter intake and microbial growth, but before that the Pé-Duro” cattle kept the weight above the established to the breed standard and without the use of protein supplementation. The Guzerá bovine found on the average weight but with the use of protein supplementation.